2013
DOI: 10.1111/ahe.12082
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Histological Organization of the Testes of the Inseminating CatfishTrachelyopterus striatulus(Steindachner, 1877) (Siluriformes: Auchenipteridae)

Abstract: The testicular morphology, spermatogenesis and occurrence of sperm in the ovarian lumen of Trachelyopterus striatulus were studied using anatomical, histological and biometric techniques. A total of 50 catfish (T. striatulus) were captured, measuring 14.9 ± 2.5 cm of standard length, body weight was 81.2 ± 34.5 g and their testes weighed 16.9 ± 6.1 g. The testes of T. striatulus are paired organs, showing two distinct regions: cranial, which shows a compact medial part and with fringes ventrally, and caudal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
1
2
0
10
Order By: Relevance
“…These characteristic can be classified as "anastomosing tubular testes" (Grier, 1993;Parenti & Grier, 2004), and as spermatogonia were distributed along the entire extension of S. parahybae seminiferous tubules, it can also be classified as "spermatogonial unrestricted", according to Grier et al (1980). These features were similar to the pattern described for other Neotropical catfish species such as Conorhynchus conirostris (Lopes et al, 2004), Pseudoplatystoma fasciatum (Batlouni et al, 2006), Pimelodella vittata (Santos et al, 2010), Trachelyopterus striatulus (Santos et al, 2014), and others.…”
Section: Discussionsupporting
confidence: 63%
“…These characteristic can be classified as "anastomosing tubular testes" (Grier, 1993;Parenti & Grier, 2004), and as spermatogonia were distributed along the entire extension of S. parahybae seminiferous tubules, it can also be classified as "spermatogonial unrestricted", according to Grier et al (1980). These features were similar to the pattern described for other Neotropical catfish species such as Conorhynchus conirostris (Lopes et al, 2004), Pseudoplatystoma fasciatum (Batlouni et al, 2006), Pimelodella vittata (Santos et al, 2010), Trachelyopterus striatulus (Santos et al, 2014), and others.…”
Section: Discussionsupporting
confidence: 63%
“…O fato dos espermatozoides de A. ucayalensis apresentarem o núcleo alongado é mais uma evidência de que é inseminador. Alguns estudos têm demonstrado que núcleo alongando é uma das características necessárias para inseminação dentre as espécies de Auchenipteridae (MEISNER et al, 2000;PARREIRA et al, 2009;SANTOS et al, 2014). Tal característica facilitaria o deslocamento do espermatozoide no lúmen ovariano e entre as lamellas ovígeras (PARREIRA et al, 2009).…”
Section: Discussionunclassified
“…The histological features of the testicles of other breeds of catfish have been described (Santos, et al, 2014;Emam and Abughrien, 2014). Similarly, a few studies have reported on the morphological features of the testicles of C. gariepinus in Nigeria (Ikpegbu et al, 2012;Eyo et al, 2012, Ajala et al, 2015.…”
Section: Introductionmentioning
confidence: 98%